LABOR EDUCATION IN CHILDREN'S SCHOOLS WITH HEARING PROBLEMS BASICS AND VOCATIONAL TRAINING OF STUDENTS (Academicia Globe: Inderscience Research, 2024)
This article deals with the organization and implementation of the process of education and training of children with hearing impairments in their schools on the basics of labor education and their chosen professions.